Tropism and Pathogenicity of Rickettsiae - Uchiyama, Tsuneo (Frontiers in Microbiology, 2012)
Rickettsiae are obligate intracellular parasitic bacteria that cause febrile exanthematous illnesses such as Rocky Mountain spotted fever, Mediterranean spotted fever, epidemic and murine typhus, etc. Although the vector ranges of each Rickettsia species are rather restricted; i.e., ticks belonging to Arachnida and lice and fleas belonging to Insecta usually act as vectors for spotted fever group and typhus group rickettsiae, respectively, it would be interesting to elucidate the mechanisms controlling the vector tropism of rickettsiae. This review discusses the factors determining the vector tropism of rickettsiae. In brief, the vector tropism of rickettsiae species is basically consistent with their tropism towards cultured tick and insect cells. The mechanisms responsible for rickettsiae pathogenicity are also described. Recently, genomic analyses of rickettsiae have revealed that they possess several genes that are homologous to those affecting the pathogenicity of other bacteria. Analyses comparing the genomes of pathogenic and nonpathogenic strains of rickettsiae have detected many factors that are related to rickettsial pathogenicity. It is also known that a reduction in the rickettsial genome has occurred during the course of its evolution. Interestingly, Rickettsia species with small genomes, such as Rickettsia prowazekii, are more pathogenic to humans than those with larger genomes. This review also examines the growth kinetics of pathogenic and nonpathogenic species of spotted fever group rickettsiae in mammalian cells. The growth of nonpathogenic species is restricted in these cells, which is mediated, at least in part, by autophagy. The superinfection of nonpathogenic rickettsiae-infected cells with pathogenic rickettsiae results in an elevated yield of the nonpathogenic rickettsiae and the growth of the pathogenic rickettsiae. Autophagy is restricted in these cells. These results are discussed in this review.